2010
DOI: 10.1002/gps.2581
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and executive functioning in stroke patients: a follow‐up study

Abstract: Symptoms of depression and executive dysfunction are highly prevalent in stroke patients and often co-occur. These patients are more at risk for poor stroke outcome, chronic depression, and cognitive deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
(78 reference statements)
1
25
1
2
Order By: Relevance
“…This is in agreement with earlier findings in patients with late-life depression,8 in which ED was associated with relapse and recurrence of depression. A smaller study in 116 patients with first-ever stroke9 also found that patients with DES showed a chronic course of depressive symptoms after 2 years.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with earlier findings in patients with late-life depression,8 in which ED was associated with relapse and recurrence of depression. A smaller study in 116 patients with first-ever stroke9 also found that patients with DES showed a chronic course of depressive symptoms after 2 years.…”
Section: Discussionmentioning
confidence: 92%
“…DES is characterised by persistence of depressive symptoms7 and unstable remission 8. In a longitudinal study with 116 patients with first-ever stroke, the DES group showed less recovery from ED and depression after 2 years compared with patients with ED only or PSD only, respectively 9. Whether DES after stroke has a distinct course regarding other cognitive domains is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One of the papers suggests that persons after cerebral stroke who experience disorders of executive functions suffer from depression more frequently than persons without such disorders. Over half (53.3%) of people suffering from both depression and disorders of executive functions were still experiencing them 2 years after the stroke, and forecasts concerning their recovery were much worse than for patients with either disorders of executive functions or depression [14]. Considerably fewer studies focus on a more precise division of executive functions and their influence on the occurrence of depression.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Si de of lesion: No association. 6,7,10,12,13,[17][18][19][20]28,29,35,[58][59][60] Associated with left-sided lesion 25 and right-sided lesion. 11,23,26 St roke severity: Increased depression with more severe stroke.…”
Section: Search Criteriamentioning
confidence: 99%